The genome sequence of a kelp fly, Coelopa pilipes Haliday, 1838 [version 1; peer review: 2 approved] - Roger Butlin; Claire Mérot (Wellcome Open Research, 2024)
We present a genome assembly from an individual male Coelopa pilipes (kelp fly; Arthropoda; Insecta; Diptera; Coelopidae). The genome sequence is 263.0 megabases in span. Most of the assembly is scaffolded into 7 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled and is 16.86 kilobases in length.